Effectiveness of Concluding Procedural Text Content Learning with Group Investigation Model based on Learning Styles - Ibrahim, Imam Ahmad; Haryadi, Haryadi (Pascasarjana Universitas Negeri Semarang, 2019)
A skill to conclude the content of procedural text owned by students to understand the meaning of the text. Learning by using investigation group model is appropriate to learning styles of students. This research aims to analyze concluding skill of students dealing with the text by using investigation group model based on students? learning styles. This quasi experimental research used several data collection techniques, such as questionnaire guidance, observation guidance, documentation, and interview guidance. The data analysis used validity and reliability tests while the sample test used normality and homogeneity test. The final data was analyzed by using one way anova to find out the effectiveness comparison of the learning based on students? learning styles. The findings showed that visual typed students got average score 79, auditory typed students 82.4, and kinesthetic typed students 77.8. Learning the skill to conclude procedural text by using the model was effective to be implemented for auditory typed students. This research is expected to enrich theoretical knowledge of learning to conclude procedural text based on the effective learning styles of students..